High-intensity action profiles between phases of play for an Australian A-League association football team - Hands, D. E.; de Jonge, X. A. K.; Livingston, G. C.; Borges, N. (International Journal of Performance Analysis in Sport, 2025)
This study determined and compared profiles of high-intensity tactical actions for different phases of play, for an Australian A-League association football team. Phases of play (build-up play; counter-attack; defensive block; counter-defending; and other) were identified using video recordings, synchronised to 10 Hz GPS data. High-intensity efforts were identified and assigned a tactical action using a validated observational framework. The percentage contribution of each action to the very high-speed activity (>19.8 km·h-1) distance for the different phases was the dependent variable. Two linear mixed models (p < 0.05) were performed (in-possession comparison and out-of-possession comparison). Generally, the tactical actions "run with ball" and "move to receive/exploit space" contributed most to build-up play; "run with ball" to counter-attack; and "close down/press" to defensive block and counter-defending phases. Significant differences between phases of play for "run with ball", "move to receive/exploit space", "support play", "close down/press" and "recovery run" were also identified. Results highlight important high-intensity tactical actions in different phases of play and demonstrate the individualised nature of phases to the contribution of tactical actions. Analysts and coaches may use such data to compare the actions players perform in different moments of matches, and this may also assist in designing training practices.